Successful Transduction of Liver in Hemophilia By AAV-Factor IX and Limitations Imposed by The Host Immune Response - Manno, Catherine S.; Arruda, Valder R.; Kaye, Robin; Nakai, Hiroyuki; Sabatino, Denise (Nature medicine, 2006)
We have previously shown that a single portal vein infusion of a recombinant adeno-associated viral vector (rAAV) expressing canine Factor IX (F.IX) resulted in long-term expression of therapeutic levels of F.IX in dogs with severe hemophilia B1. We carried out a phase 1/2 dose-escalation clinical study to extend this approach to humans with severe hemophilia B. rAAV-2 vector expressing human F.IX was infused through the hepatic artery into seven subjects. The data show that: (i) vector infusion at doses up to 2 × 1012 vg/kg was not associated with acute or long-lasting toxicity; (ii) therapeutic levels of F.IX were achieved at the highest dose tested; (iii) duration of expression at therapeutic levels was limited to a period of ∼8 weeks; (iv) a gradual decline in F.IX was accompanied by a transient asymptomatic elevation of liver transaminases that resolved without treatment. Further studies suggested that destruction of transduced hepatocytes by cell-mediated immunity targeting antigens of the AAV capsid caused both the decline in F.IX and the transient transaminitis. We conclude that rAAV-2 vectors can transduce human hepatocytes in vivo to result in therapeutically relevant levels of F.IX, but that future studies in humans may require immunomodulation to achieve long-term expression.